Tegumentary leishmaniasis and sand flies in a border area between Argentina and Bolivia - Copa, Griselda Noemi (2019)
Background: Some sand flies are of medical importance because they are vectors of Leishmania parasites that are responsible for leishmaniasis. The aim of this study was to make a retrospective epidemiological analysis of tegumentary leishmaniasis (TL), to identify Leishmania spp. from patient isolates and to describe the diversity of sand flies from a border area between Bolivia and Argentina. Methods: TL cases included in the study were diagnosed in an endemic area of the north of Argentina from 1985 to 2017. The parasites isolated were characterized by the cytochrome B method. Sand flies were captured with Centers for Disease Control traps in Aguas Blancas and Media Luna-Algarrobito localities. Results: A total of 118 cases of TL were analysed. Eight isolates were characterized as Leishmania (Viannia) braziliensis. A total of 1291 sand flies were captured, including Nyssomyia neivai, Cortelezzii complex, Evandromyia sallesi, Migonemyia migonei and Micropygomyia quinquefer. Within the area, sand flies were found in the backyards of houses. Conclusions: In this region there exists the possibility of peridomestic transmission of TL in the neighbourhoods peripheral to the urban area and in rural environments as well as the risk of transmission to travellers that pass through the customs offices.